Factors that influence students' satisfaction with their physical learning environments. Issue 3 (11th July 2016) - Wilson, Hannah Kira; Cotgrave, Alison
Abstract : Purpose: – The purpose of this paper is to identify personality types between different university disciplines, and to establish whether there are differing requirements in the design of physical learning environment. Also to identify features of the learning environment that can support a sense of community. This paper seeks to investigate the relationship between student's personality and preferences of features of the built environment. Design/methodology/approach: – Quantitative questionnaires were distributed in three university disciplines based on the variables personality, elements of the physical learning environment and features that could support a sense of community. Findings: – The analysis revealed that there are differences in preferred features within the physical learning environment for the three university disciplines within a large UK-based university. It can also be seen that there are differences in personality profiles between these three university disciplines. Features of the environment that could support a sense of community have been also identified. Research limitations/implications: – Those who are responsible for the design and refurbishment of higher education institutions may find this research useful to improve the facilities for students. To support the development of appropriate physical learning spaces through the understanding of students' requirements. Originality/value: – This paper presents a new perspective on how the development of higher education facilities can be designed to increase student experience by identifying specific features of the physical learning environment students prefer.